Countering the concealment of the criminal offenses (analysis of the legislation of the Republic of Kazakhstan) - BEKISHEV, Askhat K.; KAN, Aleksandr G. (Journal of Advanced Research in Law and Economics; Vol 7 No 7 (2016): JARLE Volume 7, Issue 7(21), Winter 2016, 2017)
The features of the regulation of the provisions, related to countering the concealment of the criminal offenses, in the legislation of the Republic of Kazakhstan are discussed in this article. The authors conducted a systematic analysis of the legislation, allowing to identify the gaps and contradictions preventing the effective application of the legal norms on disciplinary, administrative and criminal prosecution of the perpetrators for concealment of the criminal offenses. Moreover, the article reveals the problems related to the concept of ‘concealment of the criminal offense’, its use in a special legal literature. According to the results of the study, the authors came to a conclusion on the imperfection of the current legislation of the Republic of Kazakhstan in the field of counteraction of the concealment of the criminal offenses and the need for its amendment, and also offered specific suggestions for improvement of the administrative and criminal legislation. The analysis of the components of concealment of the criminal offense was performed.